DUOLINGO SPANISH USERS: DISCUSSION BOARDS USE OVER TIME - Neuschafer, Tom (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Spanish is one of the most popular foreign language subjects among learners, as there are currently 142 million users who have used Duolingo to learn Spanish. The Spanish language is projected to see even greater increases in the United States, both academically and demographically. The current research question asks, “How do individual Duolingo Spanish users use discussion boards over time among highly engaged, moderately engaged, and lower engaged users?” This study of Duolingo Spanish users is compared to a previous study about how highly engaged, moderately engaged, and lower engaged Duolingo German users use discussion boards over time. The results of the analysis showed that there were three themes: (1) highly engaged users make comments over a longer period of time over many years and have the highest proficiency in the Spanish language; (2) moderately engaged users make comments over a relatively shorter period of time during the duration of their studies; (3) lower engaged users are more likely to engage in the discussion boards socially about tangential topics over the span of months. The results of this study may inform researchers and educators on how discussion boards may facilitate language learning skills and Spanish knowledge to increase proficiency.